2014
DOI: 10.1371/journal.pone.0102246
|View full text |Cite
|
Sign up to set email alerts
|

Lantibiotic Immunity: Inhibition of Nisin Mediated Pore Formation by NisI

Abstract: Nisin, a 3.4 kDa antimicrobial peptide produced by some Lactococcus lactis strains is the most prominent member of the lantibiotic family. Nisin can inhibit cell growth and penetrates the target Gram-positive bacterial membrane by binding to Lipid II, an essential cell wall synthesis precursor. The assembled nisin-Lipid II complex forms pores in the target membrane. To gain immunity against its own-produced nisin, Lactococcus lactis is expressing two immunity protein systems, NisI and NisFEG. Here, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 59 publications
1
45
1
Order By: Relevance
“…Surprisingly, only three of 28 residues affected by nisin binding are located in the C-terminal 22 amino acids. This is in contrast to previous proposals that these C-terminal residues are very important for nisin binding and specificity (26,27) (see below). To confirm that the residues of the C-terminal domain, which show chemical shift changes upon nisin addition are functionally important for nisin binding we constructed a double mutant including two of these residues located in ␤-strand ␤4a in the center of the putative binding site.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Surprisingly, only three of 28 residues affected by nisin binding are located in the C-terminal 22 amino acids. This is in contrast to previous proposals that these C-terminal residues are very important for nisin binding and specificity (26,27) (see below). To confirm that the residues of the C-terminal domain, which show chemical shift changes upon nisin addition are functionally important for nisin binding we constructed a double mutant including two of these residues located in ␤-strand ␤4a in the center of the putative binding site.…”
Section: Resultscontrasting
confidence: 99%
“…Stein et al (24) also showed that NisI does not bind the structurally closely related subtilin. In vivo studies with truncated NisI variants (26,27) implied the C terminus of NisI and in particular the last 22 amino acids in nisin binding. To further elucidate the NisI/nisin interaction we titrated NisI with purified nisin in 15 N-HSQC experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This peptide is a bacterioc in produced by Gram-positive microorganisms which has bactericidal and bacteriostatic properties, as well as antifungal activity (7). Its effect consists in membrane pore formation of microorganisms (8). Previous reports describe the effectiveness of the NIS against C. albicans strains.…”
Section: Introductionmentioning
confidence: 99%